Juventude e meio ambiente: narrativa de jovens ambientalistas do estado da Bahia - Cristo, Hélio Souza de (2017)
This paper aims to understand and reflect on processes of socialization that represent the paths and juvenile trajectories as dispositions to engage in militancy in groups, collectives, organizations and environmental movements. Therefore, the imbrication of the school is considered as a space of formal education and socialization of the generations regarding the discussions about the environment. The research is qualitative and structured in two stages: first, with the application of a socioeconomic profile questionnaire; later, semi-structured interviews, as key points for the construction of oral narratives of young people research subjects. The relationship between youth and the environment is studied - in this research - considering the categories militant engagement and political socialization for tools that contribute to the formation and construction of projects and life trajectories of young environmentalists like social and political subjects, starting from the historical and plural concept underlying the concept of youth. Because of the peculiarity of the categories discussed, the research is conducted with young people from the state of Bahia who actively participate in movements, groups and environmental projects located in different municipalities of Bahia. Thus, research is made from a socio-historical perspective, in which the environment is understood while a field of struggles and conflicts permeated by social, political, cultural, ethical and economic issues. The path of arrival to the processes of socialization that lead or motivate young people to engage in environmental activism is marked in this paper by the discussion of issues that intersect the encounter between youth and the environment as identity and life project, ethics and environmental education, youth condition and influence of socializing agencies in the training of ecological subjects. For this, the research focuses on the theoretical ideas and assumptions that constitute a broad and significant field for the construction of dialogues between sociological and pedagogical theories, which allow us to perceive which socialization processes compose and construct the juvenile dispositions in the field of militant environmentalist engagement. Through the narratives, it has been observed that school, family, social groups, participation in unions, youth associations and youth ministries influence the youth environmental activism engagement, as well as it has been shown that reflecting and developing actions that evokes the institutionalized political participation of youth environmentalist are needed.